Epidural Clonidine Relieves Intractable Neuropathic Itch Associated With Herpes Zoster-Related Pain. Issue 4 (1st July 2003) - Elkersh, Mohamed A.; Simopoulos, Thomas T.; Malik, Atif B.; Cho, Eleanor H.; Bajwa, Zahid H.
Abstract : Objective: We present a case of intense herpes zoster-related pain and itching in the ophthalmic division of the trigeminal nerve (V1). Successful pain and itch management was achieved after insertion of a high thoracic epidural catheter with a continuous infusion of bupivacaine and clonidine. Case Report: A 73-year-old woman with metastatic malignant melanoma developed acute herpes zoster-related pain and itching unresponsive to conventional oral medications. The patient described severe and frequent attacks of lancinating pain occurring in the dermatomal distribution of the left ophthalmic division of the trigeminal nerve. She also had a disturbing itch in the same distribution as her pain. The patient had significant reduction in the frequency and intensity of the lancinating attacks after placement of a thoracic epidural catheter with continuous infusion of 1 μg/mL clonidine and 0.05% bupivacaine. The itching resolved completely as well. Conclusion: High thoracic epidural infusion of bupivacaine and clonidine was beneficial in relieving neuropathic itch in a patient with acute herpes zoster-related pain in the distribution of the trigeminal nerve.